The Hubungan Pengetahuan Ibu Tentang Gizi Dengan Kejadian Stunting Pada Balita Usia 24-59 Bulan Di Wilayah Kerja Puskesmas Landasan Ulin Tahun 2024 - Nisa, Khoirun; Kirana, Rita; Laili, Fitria Jannatul; Setiawati, Erni (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2024)
Indonesia still faces many problems related to the health of babies and children, the number of malnourished toddlers is still high, especially those experiencing stunting. The number of children under five who experience stunting in Indonesia in 2022 will be (1,321,295) with a prevalence of 21.6. According to the Banjarbaru City health profile in 2022, the highest prevalence was at the Landasan Ulin health center, namely 16.11%, or 233 toddlers experienced stunting out of 1384 toddlers whose height was measured. This study aims to determine the relationship between maternal knowledge about nutrition and the incidence of stunting in toddlers aged 24-59 months in the Landasan Ulin Health Center Working Area. This research uses quantitative survey research with a cross sectional approach. The sample in this study was 97 respondents, taken using accidental sampling technique. The independent variable in this study is maternal knowledge, the dependent variable in this study is stunting. Data collection uses questionnaires and KMS in the KIA book. Data were analyzed using the chi square test with significance a= 0,05 The results of the research show the level of maternal knowledge, from 97 respondents the results showed that the majority of maternal knowledge about nutrition was in the poor category, namely 36 (37.1%) from the results of the Chi Square statistical test carried out, it was found that there was a relationship between maternal knowledge about nutrition. with the incidence of stunting in the Landasan Ulin Community Health Center Working Area with a p value (p=0.013).The conclusion of this research is that the relationship between these variables is in the same direction, meaning that the better the mother's knowledge about nutrition, the lower the risk of toddlers experiencing stunting. So mothers' knowledge about nutrition must be increased. Keyword: Toddler stunting, mother's knowledge